PENGARUH PENGAWASAN TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS KESEJAHTERAAN SOSIAL KABUPATEN KUTAI TIMUR - Arruan, Rosalina (PREDIKSI, 2016)
The purpose of this research is to know whether the influential supervision against the spirit of employees of Dinas Pekerjaan Umum Kabupaten East Kutai. To get the data the writer do the research on the results of the research shows that the supervisions influence of the spirit of employees in Dinas Pekerjaan Umum Kabupaten East Kutai. This can be proved by the results of the data analysis rs count obtained is greater than the price table namely 0,770 > 0,456 on the level of trust 95 % for N = 14.Thus the hypothesis of this research can be accepted that the supervisions influence of the spirit of employees in Dinas Pekerjaan Umum Kabupaten East Kutai.